SEMIOTIC ANALYSIS OF MULTICULTURALISM REPRESENTATION ON CHILD CHARACTERS IN THE FILM “CUTIES” - Aldi Purnomo; Syifa Syarifah Alamiyah; Catur Suratnoaji; Juwito (JOSAR (Journal of Students Academic Research), 2022)
This study focused on the multiculturalism representation of child characters in the movie “Cuties” (2020), directed by Maimouna Doucoure. The research was interesting as it represented the child characters into multiculturalism issues which became the central problem in “Cuties”. The data was obtained in the form of movie scenes that presented the structure of multiculturalism issues. These issues were shown both visually and narratively. The study was a descriptive qualitative study using a semiotic analysis method that referred to the John Fiske model, which consisted of reality level, representation level, and ideology level. The symbols in the movie scenes represented the multiculturalism in “Cuties”. This multiculturalism could convey the diversity and differences in French society. The result of study indicated that multiculturalism was shown by the process of accepting a new culture, which was represented through attitude, behavior, narration, and other aspects in the movie through the characterization of Amy as the child character. Besides, the existence of this multiculturalism process could construct the identity formation in anyone without exception to a child.